The relationships among total body fat, bone mineral content and bone marrow adipose tissue in early-pubertal girls - L Newton, Anna (Nature Publishing Group, 2013)
Investigation of the physiologic relevance of bone marrow adipose tissue (BMAT) during growth may promote understanding of the bone-fat axis and confluence with metabolic factors. The objective of this pilot investigation was two-fold: (1) to evaluate the relationships among total body fat, bone mineral content (BMC) and femoral BMAT during childhood and underlying metabolic determinants and (2) to determine if the relationships differ by race. Participants included white and non-Hispanic black girls (n=59) ages 4–10 years. Femoral BMAT volume was measured by magnetic resonance imaging, BMC and body fat by dual-energy X-ray absorptiometry. Metabolic parameters were assessed in the fasted state. Total fat and BMC were positively associated with BMAT; however, simultaneous inclusion of BMC and body fat in the statistical model attenuated the association between BMC and BMAT. Differences in BMAT volume were observed, non-Hispanic black girls exhibiting marginally greater BMAT at age eight (P=0.05) and white girls exhibiting greater BMAT at age ten (P<0.001). Metabolic parameters conferred differential impact by race, such that, a positive association for BMAT and leptin (P=0.02) and adiponectin (P=0.002) in white girls while BMAT and insulin were inversely related in non-Hispanic black girls (P=0.008). Our findings revealed a positive relationship between BMAT, body fat and BMC, although body fat, respective to leptin, contributed partly to the relationship between BMAT and BMC. Despite large differences in total fat between non-Hispanic black and white, the relationship between BMAT and BMC was similar to white girls. However, this relationship appeared to be impacted through different mechanisms according to race.